The “Chauvinistic” Men of Julie Okoh: Victims of Feminist Bias - Imo, Edward Egbo (Journal of Gender and Power, 2018)
The paper interrogates Julie Okoh’s sense of commitment to the feminist struggle. Using her plays as case studies, the paper presents Okoh as one of the most passionate, emotional and bias feminist playwrights in Nigeria. The argument canvassed in this paper includes that in Okoh’s dramaturgy, women are portrayed far better than their men counterpart. The research is fundamentally literary in methodology and qualitative in approach with some of Okoh’s selected plays as primary source materials. The major finding in the study is that Okoh is one of the few Nigerian playwrights that have demonstrated ideological commitments in their dramaturgies. The study also observed that the feminist project, especially as portrayed in Nigerian drama, is unremorsefully hostile to patriarchy. It is in the light of the above that the paper advocates the need for Nigerian playwrights to show ideological commitment in their plays. Nigerian feminist playwrights are also encouraged to always strike a gender balance in the delineation of characters in their plays. It is hoped that such gender balancing would facilitate gender equality which the feminist project sets out to achieve.